Avascular necrosis of the hip: A unique presentation of pseudohypoparathyroidism - Valsaraj, Rahul; Goswami, Soumik; Sengupta, Nilanjan; Sahana, Pranab Kumar; Baidya, Arjun; RS, Riyas; Chowdhury, Abhra (Indian Journal of Case Reports, 2019)
Pseudohypoparathyroidism is a rare, heterogeneous disorder characterized by parathyroid hormone resistance. Its association with avascular necrosis of the hip has been reported infrequently in the past. We report the case of a 27-year-old lady with pseudohypoparathyroidism Type 1 whose initial presentation was with avascular necrosis of bilateral hip. Apart from the common clinical features of pseudohypoparathyroidism, clinicians should also be aware of the rarer resentations such as avascular necrosis. A good clinical history and physical examination are warranted for early diagnosis in order to prevent serious morbidity in thesepatients.